Microenterprises in pandemic: an approach from the entrepreneur's discourse - Ramírez Charca, Edith Diana (2020)
This study aimed to approach the behavior and expectations of micro and small enterprises (mise) in times of  pandemic of COVID-19. A qualitative study was carried out, with a phenomenological perspective, based on  the discourse of the entrepreneur who leads the mise. We worked with a non-probabilistic sample of nine  mise from diﬀerent sectors and areas of origin. The collection of information was done through an interview  and questionnaire. The interview was carried out through the call, text message and video call functions of  the social network Whatsapp; and the questionnaire, of eight items, was designed with the Google Forms  tool, to facilitate its online sending. The perceived impact of the pandemic, the action of the mise with respect  to the tax authority, the decision regarding business continuity and the decisions taken in the face of the  situation were identiﬁed as categories of analysis. As a conclusion, it was found that, in the entrepreneur's  opinion, the COVID-19 pandemic and the quarantine in the country have had a negative impact on the activity of micro and small businesses, at the level of volume of work served, sales and income.